6y+9=3(2-d)

Simple and best practice solution for 6y+9=3(2-d) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6y+9=3(2-d) equation:


Simplifying
6y + 9 = 3(2 + -1d)

Reorder the terms:
9 + 6y = 3(2 + -1d)
9 + 6y = (2 * 3 + -1d * 3)
9 + 6y = (6 + -3d)

Solving
9 + 6y = 6 + -3d

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + 6y = 6 + -9 + -3d

Combine like terms: 9 + -9 = 0
0 + 6y = 6 + -9 + -3d
6y = 6 + -9 + -3d

Combine like terms: 6 + -9 = -3
6y = -3 + -3d

Divide each side by '6'.
y = -0.5 + -0.5d

Simplifying
y = -0.5 + -0.5d

See similar equations:

| -6(3x-2)=5 | | x-46=-63 | | 5y+3y-2y=48 | | 25=9x+5-5x | | 3(5x-3)-6x=3(3x+2) | | 72+40=36+x | | 21+25m=28+18m | | 3y-6=2x+4 | | 13-17+24= | | 36-(2x+4)=2(x+6)+x | | 10-2(y-7)=3y+9 | | 150+20x=60+38x | | 32+x=-15 | | -(p+1)+5(p+8)=47 | | X+1.7=1.7x+22.9 | | 5-3(4x+3)=2 | | -(-2n-4)=5(n+2) | | 36=-9(10+1) | | 23=14+4n | | 5y^2+14=14 | | -(7n+1)-5(n+7)=12 | | 12+1.5x=15+.5 | | (7t-2)-(-3t+1)=-3-9t | | 3.5-0.02x=1.46 | | (-3)-(-14)=x | | 5x^2-25x-120=0 | | 3(u+w)+-5(u-w)= | | a(4-x)=0 | | 2x-4=8+4x | | 5(t-1)+2(t-1)=-2(t-2)+10(t+2) | | 4.9t^2+3t=5.2 | | 5*5.25=(k*5.75)+(5-k*4.50) |

Equations solver categories